KERJA SAMA AMERIKA SERIKAT DAN RUSIA DI ANGKASA LUAR: PERSPEKTIF RUSIA - Anggraini, Ajeng Novia (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2020)
This paper analyzes the U.S.-Russia cooperation of space security as two superpowers in the form of the ISS program. Most of the previous articles on this topic only explained the background of the ISS project and the process of Russia joining this project. U.S and Rusia have a “high intention” relationship during the Cold War. Even today the United States and Russia are still at odds with many things. This article uses theory of international cooperation that can explain the reasons behind Russia joint the ISS project carried out by the United States. This article shows that the reasons behind Russia’s joining the ISS program are more practical than idealistic considering that Russia has interests that must be fulfilled since the country is the successor to the Soviet space project.